2011
DOI: 10.1590/s1806-37132011000300009
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbação aguda da DPOC: mortalidade e estado funcional dois anos após a alta da UTI

Abstract: Objective: To assess ICU patients with COPD, in terms of in-hospital characteristics, two-year mortality and two-year functional status of survivors. Methods: A prospective cohort study involving patients with acute exacerbation of COPD admitted to the ICUs of two hospitals in the city of Porto Alegre, Brazil, between July of 2005 and July of 2006. At two years after discharge, survivors were interviewed by telephone in order to determine Karnofsky scores and scores on a scale regarding activities of daily liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…Mortality in eCOPD is high and we observed in our study frequent readmissions that correlated with the outcome of death, as described by Hurst, 27 Soriano, 28 and Teixeira, 29 the latter in Brazil. Teixeira says that 87.8% of the patients hospitalized with COPD had two or more comorbidities, and hospital mortality due to eCOPD was 37.7%.…”
Section: Results As N (%) or ± Sd (Min-max)supporting
confidence: 75%
“…Mortality in eCOPD is high and we observed in our study frequent readmissions that correlated with the outcome of death, as described by Hurst, 27 Soriano, 28 and Teixeira, 29 the latter in Brazil. Teixeira says that 87.8% of the patients hospitalized with COPD had two or more comorbidities, and hospital mortality due to eCOPD was 37.7%.…”
Section: Results As N (%) or ± Sd (Min-max)supporting
confidence: 75%
“…In the present study, we used the Katz index, which revealed a low degree of dependence in ADL, a finding that is consistent with those of other studies. (29,30) However, the Katz index was found to correlate negatively with the physical functioning and role-physical domains, i.e., lower scores on those domains translated to greater dependence in ADL. (29,30) The results of the present study allow us to conclude that this sample of COPD patients on LTOT had very low scores on the QoL domains of the SF-36, showing significantly impaired QoL.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of this review, the Karnofsky/Performance Status Scale Scores is the most widely used tool among researchers in Brazil (15,16,17,18). It has been largely used to assess functional status in patients with incapacitating chronic disease, such as critically ill ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of the four studies that used this tool described how it assesses functional status and also reported that the researchers who administered it had been previously trained on the use of the scale (15). Two of the aforementioned studies just reported that the researchers had been trained to administer the scale (16,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation